Strategies for Promoting Green Growth in Agriculture and Rural Districts (The 1/2th Report) - 김창길 (농업농촌부문 녹색성장 추진전략 개발(2의1차년도), 2011)
Green growth is the pursuit of economic growth, while preventing environmental degradation and unsustainable natural resource use. Korea imports about 97 percent of consumed gross energy and as a result is among the top 10 energy consuming countries. The challenge for Korea is to bring on line new sources of energy that will simultaneously permit coping with climate change and the exhaustion of fossil fuels. For as climate becomes ever warmer, international society will in an attempt to reduce greenhouse gas (GHG) emissions, further tighten environmental restrictions on energy use by means of international regulations within a framework of international cooperation. Aware of the changing circumstances in Korea and other countries, the Korean government has presented 'low carbon green growth' as a preemptive measure for coping with climate change and the looming energy crisis. In this regard it is deemed necessary to present fruitful practical strategies for promoting green growth, arrived at by means of thorough in-depth analysis, in order to successfully implement a master plan for green growth. This report details the first-year outcome of the 'Development of Strategy for Promoting Green Growth in Agriculture and Rural Districts' research project, carried out for the years 2010 and 2011 as a cooperative task under the Korea Council of Economic & Social Research Institutes. The purpose of research is to arrive at a systematic, step-by-step and fruitful strategy for promoting green growth in agriculture and rural districts by further examining the direction of discussion in Korea, and in other countries, concerning green growth. The major findings of this study are summarized below: First, GHG emissions for the agricultural sector amount to 2.9% of the gross national GHG emissions. The business as usual (BAU) figure for 2020 was estimated to reduce the figure by 0.5% from 2005 emission levels, in accordance with the IPCC guidelines for calculating the amount of GHG emissions. This exceeds the -4.0% which is a target figure for national GHG reduction and implies that it is necessary to take additional measures for reducing and absorbing GHG in the agricultural sector, e.g., technology for reducing emitted GHG from farmland, technology for storing organic carbon in soil, technology for improving enteric fermentation of ruminant livestock, etc . Second, the assessment of green growth policy in the agricultural sector revealed that the means for pursuing green growth have been properly combined, but that it remains necessary to develop policy programs to ensure the achievement of fruitful green growth outcomes and to effectively supply the requisite green technology. The assessment of green growth in the agricultural sector, a prerequisite for the detailed tasks to be promoted in the sector, showed that it is necessary to include policy means to embody the tasks, policies and systems related to green growth in rural districts in their current state. Third, survey data of farmers' and specialists' perception of green growth showed highly positive approval for the combined promotion of environmental conservation and economic growth. Respondents stated that 'furthering biomass energy' and 'spreading and supplying green technology' should be the highest priority policies. In addition, respondents evaluated as important 'the enhancement of preventive measure to cope with climate change' and 'driving the project of creating eco-friendly agriculture districts'. Fourth, an analysis of the data, a combination of specialist investigations, policy integration theory and related data, showed that it is necessary to establish the basic direction of agriculture administration in which the economy and the environment are harmonized and balanced for integrating green growth related policies, and enhancing the policy promotion system for policy integration. Indications are that the budget system related to outcome management and mid- and long-term plans are not satisfactory, and that an assessment system for green growth contribution to a specific policy is needed. Fifth, analysis of organic agriculture (the key green growth project) and of the eco-efficiency of geothermal heat pumps, to measure the level of green growth showed that organic agriculture was higher than conventional agriculture by 32.0 on the eco-efficiency index and the geothermal heat pump was higher than the petroleum heater by 5.1. Analysis of technical efficiency of organic rice farming, compared to conventional methods, on the eco-efficiency index showed that higher technical efficiency groups had higher eco-efficiency indices as well. Sixth, analysis of green productivity in the agricultural sector by means of the carbon productivity index showed increasing carbon productivity. However, this increasing carbon productivity stems from a reduction in the area devoted to rice farming and consequently a corresponding reduction in the use of nitrogen fertilizer, coupled with a rise in GDP due to an increase in the prevalence of pig farming. This is not the type of green growth obtained from the application of green technology. However, it does suggest that green growth can also be achieved by simply reducing the amount of nitrogen fertilizer applied per cultivation area, and by technology which reduces GHG emissions from ruminant livestock, etc. Seventh, a green growth potential index for rural districts was compiled with the methodology derived from the OECD index. It was shown that the green growth potential index generalizing the indices in four items of ‘green growth’, ‘green consumption’, ‘green resource basis’ and ‘environmental living quality of residents’ were found to be higher in relatively less urbanized areas, e.g., the mountainous districts in the provinces of Gangwondo and the Gyeongsangbukdo, and a part of plain fields in the provinces of Jeollanamdo and Jeollabukdo. Eighth, the low carbon policy programs to be developed will need to include elements designed to increase farming sector incomes. These farming income increases would be related to green growth in the agricultural sector i.e. GHG reduction or absorption, and other feasible programs for reducing GHG emission, e.g., using a carbon trading system. Exemplary green technology includes vertical farms for producing farm products (as produced in factories by means of a supercritical fluid system) that will allow the eco-efficient production of food, energy, raw chemicals and other products. Energy sources utilized would be either geothermal, LED and biogas plants or biomass resources, since all of these can reduce the associated energy costs and environmental loads, and would necessarily employ high-tech environmental controls and automation. Green technology should be accompanied by appropriate green finance support as this would reduce the risks involved. This is necessary as the deployment of green technology will require high levels of capital investment. Ninth, it is important to establish a policy project to determine the policy targets for green growth in the agricultural sector. The policy targets should take into account local conditions, allow for the creation of a basis for promoting the green growth policy of local bodies in rural districts that will also enrich the regional area, to set up a green resource management system for efficiently managing various green resources, to foster green industry and create green employment, and to construct a basis for using renewable energy and reducing energy. Lastly, in order to achieve the agriculture policy target, the achievement of balance and harmony between the economy and the environment, it is necessary to establish an environmental impact evaluation system for agriculture and rural districts. In other words, the policy promotion system should be reorganized. This would take the form of organizing a task force devoted to energy and environment related policies in connection with agriculture and rural districts. It would also require the establishment of a (provisional) green measures committee, whose purpose would be threefold: to enhance the connectivity between budgets and outcome management; to evaluate impact of individual policies on, and thus their contribution to green growth, and to reflect the result on budgets.